Comparison of the Implementation of the Merdeka Curriculum Between Islamic Elementary School and Islamic Junior High School - Fahlevi, Fahmi; Aripin, Syamsul (Thawalib: Jurnal Kependidikan Islam, 2025)
Modern curricula emphasize flexibility, student-centered learning, 21st-century competencies, character education, and collaboration, but they still face design, training, and implementation challenges. This study aims to analyze and compare the implementation of the Merdeka Curriculum at Islamic Elementary School Attaqwa 35 and Islamic Junior High School Attaqwa 16 in Bekasi, including their conditions, similarities, and differences. This quantitative ex post facto research used a saturated sample of 52 teachers. Data were collected through a Likert-scale questionnaire and analyzed using descriptive and inferential statistics with the help of SPSS, including normality testing, homogeneity testing, and a t-test. The results show that the implementation of Merdeka Curriculum at both Islamic Elementary School Attaqwa 35 and Islamic Junior High School Attaqwa 16 is categorized as “appropriate,” with average scores of 3.80 and 3.76, respectively. Attaqwa 35 excels in curriculum planning, while Attaqwa 16 stands out in integrated learning assessment. A significant difference is indicated by a t-value of 4.965, which is greater than the t-table value of 1.796. Attaqwa 16 demonstrates a more comprehensive implementation of the curriculum, with a valid percentage of key aspects reaching 91.7%, compared to only 33.3% at Attaqwa 35. Conclusion: The implementation of Merdeka Curriculum is more mature at the secondary level than at the primary level, influenced by planning, teacher collaboration, and community involvement.